In vitro anti-proliferative and anti-inflammatory activity of leaf and fruit extracts from Vaccinium bracteatum Thunb - Landa, Premysl; Skalova, Lenka; Bousova, Iva; Kutil, Zsofia; Langhansova, Lenka; Lou, Ji-Dong; Vanek, Tomas (Pakistan journal of pharmaceutical sciences, 2014)
The aim of this study was to evaluate in vitro anti-proliferative (tested on MCF-7, MDA-MB-231, and MCF-10A cell lines) and anti-inflammatory (evaluated as inhibition of prostaglandin E2 synthesis catalyzed by cyclooxygenase-2) effect of various extracts from Vaccinium bracteatum leaves and fruits. The highest anti-proliferative effect possessed leaf dichloromethane extract with IC50 values ranging from 93 to 198 μg/mL. In the case of cyclooxygenase-2 inhibition, n-hexane, dichloromethane, and ethanol fruit extracts showed the best activity with IC50 values = 2.0, 5.4, and 12.7 μg/mL, respectively. These results indicate that V. bracteatum leaves and fruits could be useful source of anti-cancer and anti-inflammatory compounds.
Keywords: Anti-Inflammatory Agents; Plant Leaves; nádorové buněčné linie; Antineoplastic Agents, Phytogenic; Plant Extracts; lidé; fytogenní protinádorové látky; Fruit; ovoce; Vaccinium; antiflogistika; rostlinné extrakty; listy rostlin; Cell Proliferation; proliferace buněk; Humans; Cell Line, Tumor